Regulatory and institutional dynamics in accelerating Halal product certification for achieving the SDGs in Indonesia - Nahidloh, Shofiyun; Hilmy, Masdar; Pujiati, Tri; Fajar, Fajar; Musadad, Ahmad (Universitas Islam Indonesia, 2026)
IntroductionThe rapid expansion of halal certification in Indonesia has shifted from being largely a matter of religious compliance to becoming an integral component of state policy that supports the Sustainable Development Goals (SDGs), especially those related to inclusive economic growth (Goal 8), industrial development and innovation (Goal 9), and sustainable patterns of consumption and production (Goal 12). ObjectivesThis study aims to examine how governmental regulatory frameworks drive the expansion of halal certification and to assess their broader implications for the governance of sustainable economic development.MethodThe research employs a qualitative approach based on a critical review of scholarly literature, analysis of relevant policies and institutional arrangements, and secondary data obtained from public authorities and business stakeholders.ResultsThe findings indicate that halal certification in Indonesia functions not only as a technical regulatory mechanism but also as a form of bureaucratized religious governance, through which the state institutionalizes religious authority and collective identity. Halal certification in Indonesia functions not only as a technical regulatory mechanism but also as a form of bureaucratized religious governance, through which the state institutionalizes Islamic authority and collective identity. Despite a standardized framework established by BPJPH, implementation faces structural barriers such as unequal access, limited infrastructure, and low digital literacy among MSMEs. As a public policy instrument, halal certification safeguards religious values, strengthens state legitimacy, and enhances global competitiveness. In relation to the SDGs, it contributes concretely to inclusive economic growth (SDG 8), industrial development and innovation (SDG 9), and ethical, sustainable consumption (SDG 12).ImplicationsThe study suggests that the SDGs framework can serve as an evaluative tool for assessing bureaucratic transformation in the halal industry, positioning halal certification not only as a mechanism for protecting religious values but also as part of a broader strategy for sustainable and responsible economic development.Originality/NoveltyThis study introduces a conceptualization of halal certification as bureaucratized religious governance, demonstrating how religious symbolism can be transformed into a rationalized policy instrument within the framework of sustainable development. By integrating political economy, the research provides a new analytical lens for understanding the institutionalization of religious norms through state regulation to achieve development objectives.